2015
DOI: 10.1055/s-0035-1550232
|View full text |Cite
|
Sign up to set email alerts
|

Methods in Pediatric Sleep Research and Sleep Medicine

Abstract: Several methods are used to evaluate sleep in infants, children, and adolescents including: Questionnaires and diaries, actigraphy, polysomnography, and electroencephalography which are well established. Novel approaches such as high-density electroencephalography, simultaneous electroencephalography?functional magnetic resonance imaging and nonpharmacological methods aiming for a modulation of sleep are currently only used for research. These approaches might become valuable methods for clinical application i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 103 publications
0
13
0
Order By: Relevance
“…However, the instrumentation required in studies of this detail is only found in dedicated sleep laboratories (Grigg‐Damberger et al, ). Furthermore, polysomnography requires subjects to tolerate multiple electrodes and sensors along with sleeping in a foreign, intrusive unnatural sleeping environment which poses a challenge to normal sleep patterns and is a major limitation (Mouthon & Huber, ). Thus, polysomnography is not a practical option for most infant assessment protocols particularly in the newborn nursery or in home monitoring studies, (Montgomery‐Downs, Insana, & Bond, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the instrumentation required in studies of this detail is only found in dedicated sleep laboratories (Grigg‐Damberger et al, ). Furthermore, polysomnography requires subjects to tolerate multiple electrodes and sensors along with sleeping in a foreign, intrusive unnatural sleeping environment which poses a challenge to normal sleep patterns and is a major limitation (Mouthon & Huber, ). Thus, polysomnography is not a practical option for most infant assessment protocols particularly in the newborn nursery or in home monitoring studies, (Montgomery‐Downs, Insana, & Bond, ).…”
Section: Introductionmentioning
confidence: 99%
“…& Future research in pediatric insomnia should also include an expanded repertoire of both subjective (e.g., validated questionnaires for all age groups and adapted for special populations) and objective outcome measures of sleep, including clinically meaningful biomarkers such as cardiovascular parameters, inflammatory markers, and physiologic stress measures [112,113].…”
Section: Intervention Outcomesmentioning
confidence: 99%
“…However, there are substantial barriers to examining the relationship between asthma and sleep patterns. Such studies usually need to be carried out in a special environment (for capturing sleep patterns [ 17 - 20 ]) and over a relatively long time (to accumulate enough data), which incurs high costs. Specialized and expensive equipment is typically needed to collect sleep pattern data, and participants usually have to stay in an unfamiliar sleep study facility [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%